Propuesta de una Guía Metodológica para la realización de un estudio de factibilidad Financiera del Proyecto de Inversión: Implementación de un Centro de Acopio de Plástico Reciclado”. - Salazar Escobar, Luis Jefferson (2011)
The present investigation settles in the current context of the efforts that carries out Cuba to ennoble the level of efficiency of the economy in the global context. Methodological Guide's proposal for the implementation of a center of storing of recycled plastic, it has been carried out in the Company of Recovery of Matters Cousins of Pinegrove of the River whose Central office is in the Km. 1 ½ of the highway Luis Knot in the city of Pinegrove of the River, considering that this institution doesn't have a scientific base to carry out a study of feasibility is for this reason that they don't carry out the same ones, for the elaboration of the present it guides a wide bibliography it was used, as well as the data and information gathered in the company.